KAJIAN TERHADAP MANAJEMEN PENULISAN DAN PENERBITAN BUKU TEKS PELAJARAN KURIKULUM 2013 - Benget Simamora (Jurnal Ilmiah Publipreneur, 2014)
This research aims at exploring the management of writing and publishing the school textbooks in Curicullum 2013. Data are collected through interviews, observation, and documentation. Respondents in this reseach are the authors, editors, book designers, layouters, and illustrators of Curriculum 2013. The method used in this research is a qualitative method. Data are analyzed using a descriptive-qualitative analysis technique. This research can be used as inputs to address problems manuscript textbook procurement associated with Curicullum 2013, particularly in an effort to improve the quality of school textbooks of elementary, junior high or high school. The end result of this research is that the management of writing and publishing school textbooks in Curicullum 2013 have some problems, for instance there is standard operating procedures in writing and designing.